Antibody to selected strains of Saccharomyces cerevisiae (baker's and brewer's yeast) and Candida albicans in Crohn's disease. Issue 5 (May 1990) - McKenzie, H; Main, J; Pennington, C R; Parratt, D
Abstract : IgG serum antibody was measured by ELISA in patients with Crohn's disease (15), ulcerative colitis (15), and in normal controls (15) to 12 strains of Saccharomyces cerevisiae (baker's and brewer's yeast) and to the two major serotypes of the commensal yeast Candida albicans. Antibody to 11 of the 12 strains of S cerevisiae was raised in patients with Crohn's disease but not in patients with ulcerative colitis when compared with controls (p less than 0.001). The pattern of antibody response to these 11 strains was variable, however, suggesting the likelihood of antigenic heterogeneity within the species. Antibody to C albicans was not significantly different in patient and control groups. The specificity of this unusual antibody response in Crohn's disease for S cerevisiae suggests that it is not simply the result of a generalised increase in intestinal permeability. Furthermore, because brewing and baking strains detected the response, the relevant antigen(s) are presumably common in the diet. Hypersensitivity to dietary antigens may be involved in the pathogenesis of Crohn's disease, and the role of S cerevisiae requires further investigation.